Exploring Computational and Biophysical Tools to Study the Presence of G-Quadruplex Structures: A Promising Therapeutic Solution for Drug-Resistant Vibrio cholerae - Shankar, Uma (Front Genet, 2020)
Vibrio cholerae, a gram-negative bacterium that causes cholera, has already caused seven major pandemics across the world and infects roughly 1.3–4 million people every year. Cholera treatment primarily involves oral rehydration therapy supplemented with antibiotics. But recently, multidrug-resistant strains of V. cholerae have emerged. High genomic plasticity further enhances the pathogenesis of this human pathogen. Guanines in DNA or RNA assemble to form G-quadruplex (GQ) structures which have begun to be seen as potential drug targeting sites for different pathogenic bacteria and viruses. In this perspective, we carried out a genome-wide hunt in V. cholerae using a bio-informatics approach and observed ∼85 G-quadruplex forming motifs (VC-PGQs) in chromosome I and ∼45 putative G-quadruplexs (PGQs) in chromosome II. Ten putative G-quadruplex forming motifs (VC-PGQs) were selected on the basis of conservation throughout the genus and functional analysis displayed their location in the essential genes encoding bacterial proteins, for example, methyl-accepting chemotaxis protein, orotate phosphoribosyl transferase protein, amidase proteins, etc. The predicted VC-PGQs were validated using different bio-physical techniques, including Nuclear Magnetic Resonance spectroscopy, Circular Dichroism spectroscopy, and electrophoretic mobility shift assay, which demonstrated the formation of highly stable GQ structures in the bacteria. The interaction of these VC-PGQs with the known specific GQ ligand, TMPyP4, was analyzed using ITC and molecular dynamics studies that displayed the stabilization of the VC-PGQs by the GQ ligands and thus represents a potential therapeutic strategy against this enteric pathogen by inhibiting the PGQ harboring gene expression, thereby inhibiting the bacterial growth and virulence. In summary, this study reveals the presence of conserved GQ forming motifs in the V. cholerae genome that has the potential to be used to treat the multi-drug resistance problem of the notorious enteric pathogen.